A Comprehensive Objective Evaluation Method for Handwriting Assistive Devices Using a Tablet and Digital Pen for Individuals with Upper Limb Dysfunction - Qian Li; Rui Gong; Kazunori Hase (Applied Sciences)
Traditional evaluations of handwriting assistive devices have primarily relied on user satisfaction surveys. While recent advancements in computer technologies and digital devices have enabled more objective evaluations, these methods often lack comprehensiveness. This study introduces a scientific and systematic evaluation method for evaluating handwriting assistive devices used by individuals with upper limb dysfunction. The proposed method incorporates both writing and drawing tasks, utilizing advanced computer technology and sophisticated sensors in tablets and digital pens to measure key handwriting parameters across ten indicators. These indicators are synthesized into a comprehensive score using the entropy weight method (EWM). Additionally, objective scores were compared with subjective evaluations from participants. A strong positive correlation between objective and subjective evaluations confirms the reliability of our objective method. However, statistical analysis revealed a significant mean difference between the two scoring methods, indicating that the objective method provides a more standardized and quantifiable evaluation, effectively minimizing the influence of personal biases inherent in subjective evaluations. This comprehensive evaluation method not only offers a holistic evaluation of handwriting assistive devices but also addresses the limitations of existing objective methods that tend to focus on singular aspects of performance.